Effectiveness of Large Scale Water and Sanitation Interventions: the One Million Initiative in Mozambique - Chris Elbers; Samuel Godfrey; Jan Willem Gunning; Matteus van der Velden; Melinda Vigh (Tinbergen Institute, 2012)
The One Million Initiative aims to give one million people in rural Mozambique access to clean drinking water and adequate sanitation by constructing new water points and providing sanitation training. We use panel survey data for 1600 households to analyze the health impact of the Initiative. The paper moves beyond a black box evaluation by analyzing the contribution of various channels through which the interventions affected health. To our knowledge this is the first rigorous evaluation of such a large scale program in the water and sanitation sector. We find that the water point intervention had a sizeable impact on the use of improved water sources and on the health of young children (up to 3 years), while the sanitation training had a strong impact on latrine ownership and on the health of both adults and older children.
urn:NBN:nl:ui:31-1871/38511
Keywords: I15; I18; I38; 330; impact evaluation; water and sanitation programs; health impact; Kanalisation; Wasserversorgung; Ländlicher Raum; Mosambik